2010
DOI: 10.18097/pbmc20105602244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of complexes of precursors and modulators of coenzyme q biosynthesis on functional state of old rats' heart mitochondria

Abstract: Показано, что при старении происходят изменения активности ферментных систем транспорта электронов в митохондриях сердца старых крыс и возрастает чувствительность митохондриальной поры переходной проницаемости (mitochondrial permeability transition pore, MPTP) к действию индукторов её открытия -Са 2+ и фениларсиноксида. Также наблюдается активация процессов свободнорадикального окисления липидов и белков.При введении крысам комплекса биологически активных соединений (БАС) -предшественников и модуляторов биосин… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that there is a considerable correlation between longevity and improved stress resistance (Kumchenko et al., 2009). To determine the improvement of PO‐EA on stress resistance, nematodes were exposed to three different environmental stressors (UV radiation at 180 mJ/cm 2 , thermal stress at 35 °C, and oxidative stress induced by 40 mM paraquat).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that there is a considerable correlation between longevity and improved stress resistance (Kumchenko et al., 2009). To determine the improvement of PO‐EA on stress resistance, nematodes were exposed to three different environmental stressors (UV radiation at 180 mJ/cm 2 , thermal stress at 35 °C, and oxidative stress induced by 40 mM paraquat).…”
Section: Resultsmentioning
confidence: 99%
“…The metabolite 4-HBA has shown anticancer and neuroprotective effects [37,38,39,40]. Moreover, this compound is a precursor of the coenzyme Q10, showing cardioprotective properties [41,42].…”
Section: Discussionmentioning
confidence: 99%